Multipass cell for high-power few-cycle compression - Mueller, Michael; Buldt, Joachim; Stark, Henning; Grebing, Christian; Limpert, Jens (Optics Letters, 2021)
A multipass cell for nonlinear compression to few-cycle pulse duration is introduced composing dielectrically enhanced silver mirrors on silicon substrates. Spectral broadening with 388 W output average power and 776 μJ pulse energy is obtained at 82% cell transmission. A high output beam quality (M2 <1.2) and a high spatio-spectral homogeneity (97.5%), as well as the compressibility of the output pulses to 6.9 fs duration, are demonstrated. A finite element analysis reveals scalability of this cell to 2 kW average output power.
CRIS-Team Scopus Importer:2023-04-20